Pengaruh Reward Terhadap Kinerja Sumber Daya Manusia: Sebuah Literature Review - Muhammad Erikko Abimayu; Dora Amelya; Debbyanggraiansyah Debbyanggraiansyah; Mega Rahmi; Teguh Aprianto (CV. ULIL ALBAB CORP, 2024)
Business developments in this technological era create very tight competition between each other. Human resources is one of the qualities that influences the running of the business. What is meant by human resources are workers within the scope of the business. For this reason, the quality of human resources must be of high quality and maintained. This research analyzes the influence of rewards on human resource performance. Researchers used a literature review method involving several relevant sources. From the research conducted, results were obtained that rewards influence human resource performance. With rewards, workers will also be more enthusiastic, disciplined, and careful in doing their work.